(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article examines institutional and legal mechanisms for preventing tax base erosion caused by undisclosed profits through foreign legal structures controlled by domestic taxpayers. It analyzes global experiences with anti-avoidance measures—especially the regulation of foreign-controlled entities—and assesses how such frameworks can be adapted to Uzbekistan. Particular attention is given to the role of digital oversight, international data exchange systems, and beneficial ownership declarations. The study proposes regulatory steps for Uzbekistan to strengthen its fiscal transparency infrastructure and integrate CFC-related tax controls with global standards.